ADDITIVITY OF VOLUME COMPONENTS OF TREE BOLES - Behling, Alexandre; David, Hassan Camil; Demétrio, Clarice Garcia Borges; Sanquetta, Carlos Roberto; Corte, Ana Paula Dalla; Woycikievicz, Antonio Pedro Fragoso (Floresta, 2019)
Bark volume and inside-bark volume are components of tree boles. Thus, equations for volume components must be additive so that their estimates are compatible to the total volume. This research aimed to present a method based on the additivity principle such that this condition is met. Volume modeling was performed using data from black-wattle (Acacia mearnsii De Wild.) stands. We treat the inside-bark volume and bark volume as components of bole volume. The method known as Nonlinear Seemingly Unrelated Regressions (NSUR) ensured the condition for which the component values estimated by means of non-linear equations were additive and equivalent to the total value, demonstrating that the method is appropriate.